If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 3w = -2 Solving 4 + 3w = -2 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3w = -2 + -4 Combine like terms: 4 + -4 = 0 0 + 3w = -2 + -4 3w = -2 + -4 Combine like terms: -2 + -4 = -6 3w = -6 Divide each side by '3'. w = -2 Simplifying w = -2
| 7+C=9 | | -48/(-6)= | | 36/(-3)= | | (x^3+2)(x^3-2)= | | 8x^2+8=2x | | -2x/3-4 | | 5y-7=18y+97 | | (-5)(-3)(-1)(3)= | | -19-(-49)= | | (-4)(-9)= | | 5h+4=8 | | 3n+24+2n+31=180 | | 12(-6)= | | 9a-2=5a+22 | | 9x=7x-4 | | 10x^2-2=-20 | | -2y-14=-10 | | -36/9= | | -(6k+8)=7k-6(k-1) | | -24+20w=73 | | -3x-16= | | (2x)/(x+1)=(2x-1)/x | | -2(3v-1)-4(v+8)=-7v-6v | | 1/2x-4=-4 | | -63(-9)= | | 7-6(c-1)+3(3-4c)= | | 21m^2+28m=0 | | 9ln(x^2)=8 | | -r=30 | | 4(1-7m)=7(1-3m)-4m | | 4(2+p)=-(2p+4) | | 4(2+p)=-2(p+4) |